Memories Denied - Paju, Imbi (Finland : Koljonen, Nina ; Runk, Pille, 2005)
This historical-psychological documentary film tells the story of the experiences of the director´s mother and her twin sister in a totalitarian society under Stalinism, Soviet occupation and terror, when repressing memories was the only method of self-defense. The film is an analysis of memory which goes through violent personal memories of the Second World War sixty years after Stalin’s concentration camps and Soviet terror. In the documentary, the director depicts her mother’s past and, at the same time, that of all Estonia. Although it is still hard to talk about the unresolved past which crosses generation lines, this journey must be completed in order for the community to heal from the wounds of history.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films